ANALISIS SISTEM PENGAMAN ARUS LEBIH PADA PENYULANG ABANG DENGAN BEROPERASINYA PLTS PADA SALURAN DISTRIBUSI TEGANGAN LISTRIK 20 KV DI KARANGASEM - Nurcahyadi, Made Benny; Rinas, I Wayan; Pemayun, A.A.Gede Maharta (Jurnal Teknologi Elektro; Vol 16 No 1 (2017): (January - April) Majalah Ilmiah Teknologi Elektro, 2016)
Abstract? F eeder Abang is one of the feeders in Bali which is a source of electrical energy coming from the substation Amlapura. Connection of new power generation units to the distribution network can increase the short-circuit current in the event of interference on the channel. Simulation of short circuit at the ETAP program is done with two simulations are simulated short circuit without the operation and after the operation of solar power generation. The results of the analysis of short circuit without the operation of the solar power generation obtained short-circuit current is greatest at point 1 B217 bus at 1026 and 1224 A with the operation of the solar power generation. Without the operation of solar power generation the smallest short-circuit current at the point 5, namely the B366 bus of 792 A and 882 A with the operation of the solar power generation. Increased short circuit resulted in changes in working time of relays at five points by interference from 0.123 to 0.131 seconds without the operation of solar power, while the operation of the solar power generation, working time of relay changes into 0.117 to 0.127 seconds Keyword : solar power generation, short-circuit, relay     Intisari ? Penyulang Abang merupakan salah satu penyulang di pulau Bali yang sumber energi listriknya berasal dari Gardu Induk Amlapura . Penyambungan unit pembangkit listrik yang baru ke jaringan distribusi dapat meningkatkan arus hubung singkat apabila terjadi gangguan pada saluran. Simulasi gangguan hubung singkat pada program ETAP dilakukan dengan dua simulasi yaitu simulasi gangguan hubung singkat tanpa beroperasinya PLTS dan setelah beroperasinya PLTS. Hasil analisis gangguan hubung singkat tanpa beroperasinya PLTS didapat arus hubung singkat terbesar pada titik 1 yaitu bus B217 sebesar 1026 dan 1224 A dengan beroperasinya PLTS. Tanpa beroperasinya PLTS arus hubung singkat terkecil pada titik 5 yaitu pada bus B366 sebesar 792 A dan 882 A dengan beroperasinya PLTS . Peningkatan arus hubung singkat mengakibatkan perubahan waktu kerja dari rele di lima titik gangguan sebesar 0,123 - 0,131 detik dengan kondisi tanpa PLTS, sedangkan dengan beroperasinya PLTS perubahan waktu kerja rele yaitu 0,117 – 0,127 detik. Kata Kunci : PLTS, Hubung Singkat, Rele DOI: 10.24843/MITE.1601.09
Keywords: PLTS, Hubung Singkat, Rele